Ellipsis in English Coordinated Clauses in the Novel Entitled 44 Scotland Street by Alexander McCall Smith - Sandy Wangi, Kadek; Tika, I Ketut; Budiarsa, I Made (Humanis, 2018)
The title of this undergraduate thesis is Ellipsis in English Coordinated Clauses in the Novel Entitled 44 Scotland Street by Alexander McCall Smith. The aims of the study are to classify the types of ellipsis and to analyze the position of ellipsis in coordinated clauses. The data of this study were in the form of the English coordinated clauses with coordinating conjunction and, or , and but which were found in a novel entitled 44 Scotland Street by Alexander McCall Smith. The data were collected by using documentation method which was done by close reading on the data source, taking note, and continued by classification. This study used the theory of ellipsis proposed by Quirk, et al (1972) presented by using qualitative method in analyzing the data. The collected data were identified according to the categories of the types and the occurrence of ellipsis in coordinated clauses. This study used descriptive method in presenting the data. The result of this study shows that the types of ellipsis in coordinated are divided into six major namely: ellipsis of subject, ellipsis of auxiliary, ellipsis of subject and auxiliary, ellipsis of predication, ellipsis of head of noun phrase, and ellipsis of subject complement.  Ellipsis of subject is the most frequently used type of ellipsis that occur in the data. The ellipsis can occur in the first and in the subsequent clauses in coordinated clauses. However, the ellipsis in the data is mostly anaphoric with the realized items in the first of a series of the clauses.